Synthesis and evaluation of photophysical and electrochemical properties of vinyl chalcogenide derivatives of phenothiazines. (February 2022) - Dilelio, Marina Cardoso; Kaufman, Teodoro S.; Iglesias, Bernardo Almeida; Silveira, Claudio C.
Abstract: The Wittig-Horner mediated syntheses of phenothiazines carrying vinylsulfide and vinylselenide motifs attached to the aromatic ring(s) or connected to the central nitrogen atom of the heterocycle, and the subsequent study of their photophysical and electrochemical properties, are reported. These compounds were obtained as mixtures of geometric isomers, in good to excellent yields. To complete the study, a small set of vinylsulfoxide and vinylsulfone derivatives was also prepared from the corresponding oxidized phosphinoxides. The photophysical properties of the compounds were examined in solvents of varying polarity, in which they presented absorption maxima in the UV region, with molar absorptivity coefficients compatible with symmetry-allowed π–π* electronic transitions. The heterocyclic derivatives were fluorescent. Compounds bearing vinylsulfide moieties associated to the nitrogen atom of the heterocycle displayed less intense fluorescence than the phenothiazine derivatives carrying vinylchalcogenides bonded to the aromatic ring; the latter also exhibited more red-shifted absorption spectra, and Stokes shifts in the range 6115–8170 cm −1 with weak dependence of solvent polarity. The sulfoxide and sulfones displayed more red-shifted spectra than the corresponding sulfides. The cyclic voltammograms of all derivatives exhibited a common pattern of reversible or quasi -reversible processes in the anodic region, related to the phenothiazine unit. Graphical abstract: Image 1 Highlights: Wittig-Horner mediated synthesis of vinyl chalcogenide derivatives of phenothiazine. The vinyl chalcogenides were photochemically and electrochemically characterized. Vinyl chalcogenide moieties bound to the phenothiazine induced large Stokes shifts. 3- and 3, 7-Substituted phenothiazines displayed high fluorescence quantum yields. Electrochemical analysis revealed phenothiazine moiety as the electroactive center.